Pengaruh Penambahan Ball Mouth Pada Pompa Aliran Aksial Pvc 6 Inci Bertenaga Motor Listrik 1.5 Kw - rendi; Arifin, Jainal; Maulana, Ahmad (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
Axial pumps are a type of centrifugal type water pump that is widely used by the agricultural and fishing industries to move water in large capacities. This research aims to study the effect of adding Ball Mouth to an axial flow pump designed and made from 6 inch PVC pipe powered by a 1.5 kW electric motor. This research uses an experimental method, namely by testing 3 prototype axial pumps using Ball Mouth model A, model B and without using a ball mouth. The test was carried out by varying the number of propeller blades, namely blade 2, blade 3 and blade 4. Data was taken by measuring volume flow rate via U-Notch and electrical power consumption via an Ampermeter measuring instrument. The results show that the addition of the Ball Mouth, especially model B, increases the volume flow rate and pump efficiency significantly. However, the differences between models A and B are not consistent across blades, indicating the importance of design adjustments for optimal results.